'I Stuck to Plymouth, Plymouth Stuck to Me': Nancy Astor, Electioneering and Female Parliamentary Candidacy. Issue 2 (10th September 2020) - Berry-Waite, Lisa
In November 1919, Nancy Astor won a Plymouth Sutton by-election, becoming the first woman MP to take her seat in the House of Commons. Astor was MP from 1919 to 1945 and won seven elections in total. A vast amount of material has been written on Astor's 1919 election campaign given its historical significance, but her subsequent elections remain a neglected area of study. This article focuses on all seven of Astor's election campaigns, exploring how her electioneering evolved over time and the distinctive features of each of her elections. Furthermore, it examines the interconnected relationship between Astor's gender, class, party, and nationality, and looks at the electability of women more broadly. It argues that all seven of Astor's election campaigns centred around broad principles of morality, social justice, and her long-standing commitment to Plymouth, coupled with anti-socialist rhetoric. Indeed, Astor presented little in the way of detailed policy plans and promises for the future. Despite standing as the official Conservative candidate, Astor was fiercely independent. She was a politician of conviction who championed issues of personal interest, both to herself and the Plymouth Sutton constituency. Astor's career as a campaigner is worthy of note given no other female candidate came close to winning seven elections in the interwar period, considering the multitude of obstacles female candidates encountered.